Respuesta :

Answer: D

Step-by-step explanation:

Answer:

A

Step-by-step explanation:

Calculate the lengths of JK and JL using the distance formula

d  = [tex]\sqrt{(x_{2}-x_{1})^2+(y_{2}-y_{1})^2 }[/tex]

with (x₁, y₁ ) = J(2, 1) and (x₂, y₂ ) = K(- 4, 2)

JK = [tex]\sqrt{(-4-2)^2+(2-1)^2}[/tex]

     =  [tex]\sqrt{(-6)^2+1^2}[/tex]

     = [tex]\sqrt{36+1}[/tex]

     = [tex]\sqrt{37}[/tex] ≈ 6.1 units

Repeat with (x₁, y₁ ) = J(2, 1) and (x₂, y₂ ) = L(7, 4)

JL = [tex]\sqrt{(7-2)^2+(4-1)^2}[/tex]

    = [tex]\sqrt{5^2+3^2}[/tex]

    = [tex]\sqrt{25+9}[/tex]

    = [tex]\sqrt{34}[/tex] ≈ 5.8 units

Thus JK is longer than JL →  A

ACCESS MORE